2004
DOI: 10.1111/j.1753-4887.2004.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids and Cardiovascular Health

Abstract: Epidemiologic studies have shown a beneficial association between polyunsaturated fatty acid (PUFA), specifically linoleic acid (C18:2, n-6), intake and cardiovascular disease morbidity and mortality. Clinical studies have shown that n-6 PUFAs have the most potent cholesterol-lowering effects of the individual fatty acid classes, and emerging evidence suggests that PUFAs have favorable effects on postprandial lipemia. However, some studies suggest that high intakes of linoleic acid may have adverse effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(62 citation statements)
references
References 58 publications
1
56
0
5
Order By: Relevance
“…With regard to dietary fat, there is growing consensus concerning the beneficial effects of MUFA and/or PUFA in terms of preventing diabetes and CVD (21)(22)(23)(24) , but the detrimental effect of SFA is still controversial (25,26) . In our study, the highest total fat intake was found in the vegetal/fat group, followed by the animal products group.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to dietary fat, there is growing consensus concerning the beneficial effects of MUFA and/or PUFA in terms of preventing diabetes and CVD (21)(22)(23)(24) , but the detrimental effect of SFA is still controversial (25,26) . In our study, the highest total fat intake was found in the vegetal/fat group, followed by the animal products group.…”
Section: Discussionmentioning
confidence: 99%
“…However, application of the 1-week withdrawal period in birds fed FO diets did not significantly affect lipoproteins. In recent studies, lipoproteins like LDL play a critical role in atherosclerosis and coronary heart disease have been demonstrated (Kris-Etherton et al, 2004;Ló pez-Garcia et al, 2005). It is documented that serum HDL level is capable of decreasing the negative effects of high blood cholesterol (Alparslan and Ö zdogan, 2006).…”
Section: Serum Biochemical Valuesmentioning
confidence: 99%
“…The supplementation of fish extracts (oils) in animal reproduction would provide not only the physiological needs of animals, but also adequate quantities of the diet composition of humans (Kris-Etherton et al, 2004). Recent epidemiologic studies suggest that dietary consumption of EPA and DHA affects the relative concentrations of n-6 and n-3 PUFAs and, consequently, cardiovascular disorders, presumably because of their structural and biochemical involvement in pathophysiological processes and the associated improved performance (Kris-Etherton et al, 2004;Alparslan and Ö zdogan, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Doymuş yağlara göre kıyaslandığında; TDYA, ÇDYA gibi toplam kolesterol ve düşük yoğunluklu lipoprotein [low density lipoprotein (LDL-K)] kolesterol düzeylerini azaltabilmektedir. 35,36 TDYA'nın plazma yüksek yoğunluklu lipoprotein [high density lipoprotein (HDL-K)] kolesterol seviyesini artırabildiği ve trigliserid seviyesini azaltabildiği de saptanmıştır. 37 Balık ve deniz ürünlerinde bol miktarda bulunan ÇDYA'dan olan n-3 yağ asitleri de trigliserid, toplam kolesterol ve LDL-K seviyelerini azaltabilmekte, HDL-K seviyesini ise artırabilmektedir.…”
Section: Doymamış Yağlarunclassified